Preharvest and Postharvest Factors Improving Horticultural Crops Quality and Shelf-Life (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The quality and safety of fresh horticultural products involves their own development, environmental factors, and interactions with postharvest pathogens. Effective pre- and post-harvest techniques play a key role in improving the quality of fresh horticultural products, and this reprint focuses on the understanding of the pre- and post-harvest factors that affect postharvest quality, disease, ripening and senescence, and the shelf life of horticultural crops. This reprint contains papers from the aspects of field management and pre- and post-harvest treatments, and new methods are proposed to improve the quality and shelf life of different fresh horticultural products.